STUDI KASUS PERBANDINGAN PRODUKTIVITAS PEMODELANBIM: PRECAST VS TRADISIONAL - Reza Rahardian; Haromi Ma’mun; Naimatunnisa; Belly Belly Saptiansyah; Yongki Alexander Tanne; Falderika (Program Studi Teknik Sipil, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2025)
Productivity in Building Information Modeling (BIM) modeling plays a key role in project efficiency. However, the comparison between precast and traditional methods is still rarely studied. This research investigates the productivity comparison between BIM modeling methods and traditional construction execution on the Rumah Sakit Mitra Pumbon Subang project. The study uses a descriptive quantitative approach with data collected through 3D modeling (Autodesk Revit), scheduling (Microsoft Project), and 4D simulation (Autodesk Navisworks). The results show that BIM modeling requires more time (28 days) compared to the precast method (41 days) due to design complexity and more detailed object modeling in Revit compared to traditional CAD drawings. Meanwhile, the traditional construction method takes longer (153 days) compared to the precast method (137 days), due to the standardization advantages of precast work. In terms of material needs, BIM provides more precise calculations using the